The neural networks apply in the area of diagnostic systems - Musil, Michal (Univerzita Pardubice, 2009)
This contribution deals with possibility exploitation artificial neural networks in the area of diagnostic systems. Is concerned application recognition symptom disturbances in diagnostic signals. Neural networks are learnt on failure-free waveform of signal and next waveform of signal with appearance symptom reason about disturbances in diagnostic system. Comparsion input and predicate signal and comparison output of separate networks is identified concrete disturbance in monitoring system.
Keywords: neural networks; diagnostic systems; failure-free waveform